Instrumentation Monitoring For Heavy Metal Detection In Batik Industry - Kodi, Saravanan Thunsh (Universiti Sains Malaysia, 2019)
A real-time monitoring of heavy metals in water environment is crucial nowadays because it is the biggest contributor to water pollution and leads to many diseases to humans. In contrast with organic pollutants, heavy metals cannot be biologically or chemically degraded at all, and thus may either accumulate locally or be transported over long distances. The wastewater discharge from Batik industries became a significant issue on the sustainability of the environment for the next generation. Heavy metal that exist in wastewater is an extremely dangerous pollutants to ecosystem and toxic to human health. The industry faces difficulty to monitor the waste discharge because the usual practice for analyses heavy metal work in central laboratories causes delay time and contamination of sample during transportation to central of laboratories leads to inaccuracy in data monitoring of heavy metals in water environment. This study proposes the development of instrument device to real-time monitoring heavy metal using an electroanalytical technique. This project introduced mathematical algorithm to represent the existing metal concentration in the solution based on statistical analysis from the data collection using laboratory control sample. In order to ensure the result more robust, the others significant parameter such as temperature and pH were considered during mathematical formulation development. For field work application, the effect of viscosity, pressure drop and condition of pipe for steady flow. The flow changes affect the measurement sensor reading due to the turbulent flow. However, the flow change inside pipe network can change the physical disturbance that can lead to inaccuracy of data measurement.